The Violation of Maxims and The Conversational Implicature in ‘Hichki 2018’ Movie - Hendra Efendi; I Made Suta Paramarta; Risman Iye (Jurnal Wawasan Sarjana, 2023)
In a movie, the characters often violate maxims and conversational Implicatures to boost a dramatic impression of the movie. This research was conducted to analyze the violation of maxims, in which the violations found can cause conversational implicature. The research is a qualitative study. The research subject is an inspirational Bollywood film entitled "Hichki 2018". The data is in the form of utterances in the movie that contain maxims violations and conversational implicature. Data collection is conducted in a series of steps: downloading the film and its script, observing the film's utterances and selecting the data from the script. The data analysis is done by compiling data in narration form, analyzing data, and writing a conclusion. This research shows that twenty-seven utterances contain three types of violations of maxims. They are the maxim of quantity, the maxim of relevance, and the maxim of manner. Maxim of manner is the most frequent violated maxim. The Conversational Implicatures found outside those caused by the violation of maxims are in five utterances. The violation of maxims in this movie gives a deeper meaning to the audience, making this story more dramatic through its dialogues